THE EFFECTIVENESS OF GROUP COUNSELING IN ENHANCING SELF-CONFIDENCE AMONG ELEMENTARY SCHOOL STUDENTS - Fauzi Aldina; Ming Pong; Aom Thai; Bernardus Agus Rukiyanto (Yayasan Adra Karima Hubbi, 2025)
Self-confidence is a critical component of children’s personal and academic development, enabling them to engage actively in learning and social interactions. Elementary school students with low self-confidence often face challenges in expressing themselves, participating in group activities, and achieving academic success. This study investigates the effectiveness of group counseling in enhancing self-confidence among elementary school students. The research employed a quasi-experimental design with a pre-test and post-test control group. The sample consisted of 60 students identified as having low self-confidence, divided equally into an experimental group that received group counseling sessions and a control group following standard classroom activities. Data were collected through self-confidence questionnaires, behavioral observation sheets, and teacher interviews. The findings revealed a significant increase in self-confidence scores in the experimental group compared to the control group. Students in the experimental group demonstrated greater willingness to participate in discussions, share ideas, and take initiative in various school activities. These results confirm that group counseling effectively fosters a supportive environment where students can build self-assurance through peer interaction and guided facilitation. The study concludes that group counseling is a valuable tool for addressing self-confidence issues and recommends its broader implementation in elementary schools.